2008
DOI: 10.2139/ssrn.1098847
|View full text |Cite
|
Sign up to set email alerts
|

Do Higher Rents Discourage Fertility? Evidence from US Cities, 1940-2000

Abstract: This paper documents the existence of a negative cross-sectional correlation between the price of living space and fertility using U.S. Census data over the period 1940-2000. This correlation is not spurious, nor does it reflect the tendency of larger families to locate within lessexpensive areas of a given metropolitan area. We examine the extent to which the results reflect the sorting of married couples across metropolitan areas on desired fertility. The relationship between the unit price of living space a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Simon and Tamura () have studied the link between rent levels and fertility in American cities from 1940 to 2000. They cite Alfred Marshall as a researcher who singled out housing as an important factor for fertility as early as the early 20th century.…”
Section: Housing Market Effects On Fertilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Simon and Tamura () have studied the link between rent levels and fertility in American cities from 1940 to 2000. They cite Alfred Marshall as a researcher who singled out housing as an important factor for fertility as early as the early 20th century.…”
Section: Housing Market Effects On Fertilitymentioning
confidence: 99%
“…The evaluation of the panel‐based estimates will furthermore be used to address a question that has lately received increased attention, namely to what extent housing market conditions, apart from being influenced by demographic shifts, also are shaping demographic trends, fertility in particular. Effects of house prices on fertility have been demonstrated for the USA (Simon and Tamura, ; Clark, 2011) and for Hong Kong (Yi and Zhang, ). Likewise, in a study of the Nordic countries, Kulu et al .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have showed that the cost of homeownership impacts on the decisions around fertility (Anderson et al, ; Clark & Drever, ; Courgeau & Lelièvre, ; Kulu & Vikat, ; Mulder & Wagner, ; Mulder & Wagner, ; Sato, ; Simon & Tamura, ), which is particularly relevant to Australian policy debates. High‐cost urban centres was found to drive relocation to more affordable suburban or rural areas to accommodate increasing family size (Kulu & Vikat, ), and the high cost of homeownership increased the cost of rearing children and was associated with delayed fertility (Clark, ; Courgeau & Lelièvre, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…High‐cost urban centres was found to drive relocation to more affordable suburban or rural areas to accommodate increasing family size (Kulu & Vikat, ), and the high cost of homeownership increased the cost of rearing children and was associated with delayed fertility (Clark, ; Courgeau & Lelièvre, ). Similarly, the price of living space, measured by rent per room at the metropolitan area level, has shown a negative cross‐sectional relationship with fertility, which implies that house prices may affect the location or childbearing decisions of families (Simon & Tamura, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Housing policies in the Netherlands, have expanded to provide a sizeable rental provision for students and young adults, which has produced an inadvertent fertility increase (Mills, 2015). U.S. Census data shows that the price of living space calculated by rent per room has a negative correlation with the level of fertility among younger families during the period between 1940 and 2000 (Simon & Tamura, 2009). Assuming that housing is a significant portion of overall household budgetary decisions, which also include childraising costs, the increase in house prices could present an adverse effect on fertility (Mulder & Billari, 2010).…”
Section: Backgroundsmentioning
confidence: 99%